Evaluating the frequency of upgrade to malignancy following surgical excision of high‐risk breast lesions and ductal carcinoma in situ identified by core needle biopsy. Issue 1 (20th November 2018) - Allen, Ahkeel; Cauthen, Allison; Dale, Paul; Jean‐Louis, Christopher; Lord, Allison; Smith, Betsy
Abstract: Excision of high‐risk breast lesions (HRL) continues to be standard of care. Previous studies have shown that HRLs can be upgraded to carcinoma in situ (CIS) or invasive carcinoma (IC) upon excision. A single institution retrospective review was conducted to determine the rate of upgrade of HRLs and ductal carcinoma in situ (DCIS) identified on image‐guided biopsy upon excision. Eight hundred and fifty‐seven patients who underwent core needle biopsy (CNB) following the detection of suspicious lesions (BI‐RADS IV) on mammograms were identified. HRLs and DCIS warranting subsequent surgical excision were found in 129 of 857 patients (15.1%). Overall, 19.6% (10/51) of DCIS, 52.4% (11/21) of ADH, and 17.6% (3/17) of papillomas were upgraded on surgical excision. A statistically significant difference was found between the concordant and discordant groups regarding the number of cores obtained ( P  = 0.01) and the needle size used to retrieve specimens on CNB ( P  = 0.01). This study reveals an upgrade rate of 26.7% of HRLs and DCIS diagnosed by CNB on surgical excision and emphasizes the continued use of large bore needles with an adequate number of core specimens when investigating a suspicious breast lesion.